Outward FDI and home country employment - Riccardo Crescenzi; Roberto Ganau; Michael Storper (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2023)
New research shows a positive link between Outward FDI and domestic employment in USA local labor markets where investing companies are located. Job creation at home and abroad are complementary, especially in less developed regions. Investment Promotion Agencies should facilitate active internationalization of domestic firms while reinforcing their local linkages.
Keywords: 330